Degrading cassava mill effluent using aerated sequencing batch reactor with palm kernel shell as medium - Nurudeen Samuel Lawal; Kolawole Ogedengbe; Babatunde Olusola Adetifa; George Nnaemeka Anyanwu (Brawijaya University, 2019)
Local cassava agro-processing industries in Nigeria generate toxic organic effluent with negative environmental impact if disposed without adequate treatment. This study examines the performance of a lab-scale aerated sequencing batch reactor (SBR) in degrading cassava mill effluent using palm kernel (Elaeis guineensis) shell (PKS) as biofilter media. Wastewater samples were collected before and after flowing through each compartment at hydraulic retention times of 3, 5 and 7 hours. Continuous aeration and nature-based degradation of the effluent recorded overall removal efficiencies of 73.5% (Hydrogen cyanide), 70.59% (BOD), 69.18% (COD), 29.93% (Turbidity), 4.92% (Sodium), 25% (Magnesium) and 14.32% (Calcium) respectively. Effluent electrical conductivity (EC) slightly increased by 7.84%. The Sodium Adsorption Ratio (SAR) of the treated wastewater ranged from 6.9 to 7.3 while the final pH ranged from 4.5 to 4.6. The values of EC, BOD and COD were significantly different (P<0.05) along the treatment sequence, confirming the effectiveness of the chambers in reducing these pollutants. Despite achieving high removal efficiencies, the final values of most parameters still fall short of the local permissible limit signifying operational limitations and the need to optimize the system to reduce key contaminants to safe disposal limits